Ability of EDI-2 and EDI-3 to correctly identify patients and subjects at risk for eating disorders. (December 2015) - Segura-García, Cristina; Aloi, Matteo; Rania, Marianna; Ciambrone, Paola; Palmieri, Antonella; Pugliese, Valentina; Ruiz Moruno, Antonio José; De Fazio, Pasquale
Abstract: Aims: The prevention and early recognition of eating disorders (EDs) are important topics in public health. This study aims to compare the efficacy of the Eating Disorder Inventory 2 (EDI-2) with the new version, EDI-3 in recognising patients and identifying subjects at risk for EDs. Methods: The EDI-2 and EDI-3 were administered to 92 female patients with ED and 265 females from a population at risk for EDs. Experienced psychiatrists in this field held blind interviews with participants by means of the SCID-I to determine the diagnosis. Results: According to the cut-offs suggested by the authors, the EDI-3 correctly identified nearly all of the ED patients (99%), while the EDI-2 divulged less than half (48%). Both versions of the test showed comparable capability to identify participants at risk for EDs but the EDI-3 seemed slightly more reliable than the EDI-2. Conclusions: The EDI-2 remains a valid and very specific test. However, the new EDI-3 seems to be experimentally superior, because it typifies nearly all patients across the ED span, including those with Binge Eating Disorder and Eating Disorder Not Otherwise Specified. In addition, it appears to be more reliable. Highlights: We compare the efficacy of EDI2 and EDI3 in identifying Eating Disorders (EDs). EDI-3 correctly identified nearly all of the ED patients (99%) including ED-NOS. EDI-2 correctly identified less than half of ED patients (48%) including ED-NOS. EDI-3 is slightly more reliable to identify subjects at risk for EDs. EDI-3 seems to be experimentally superior and more reliable than EDI-2.